Critical Assessment of Video Production in Teacher Education: Can video production foster community-engaged scholarship? - Yang, Kyung-Hwa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
In the theoretical framework of production pedagogy, I reflect on a video production project conducted in a teacher education program and discuss the potential of video production to foster community-engaged scholarship among pre-service teachers. While the importance of engaging learners in creating media has been emphasized, studies show little evidence of its pedagogical usefulness. In particular, what learners actually learn through video production remains relatively unknown. In this article, I examine pre-service teachers’ reflections on their participation in the video project and argue that, to promote community-engaged scholarship, teacher educators should encourage pre-service teachers to interact with people in their communities in making videos.